Pengaruh Digital Marketing dan Customer Relationship Marketing Terhadap Loyalitas Konsumen Pulma House Medan - Mayzira, Chantika; Syahrial, Hery (Universitas Medan Area, 2024)
This research aims to determine the influence of digital marketing and customer relationship marketing on consumer loyalty at Pulma House Medan. This type of research is quantitative with an associative approach. The data used is primary data or questionnaires and the data analysis method uses SPSS 25. The population in this study is visitors to Pulma House for the period January 2022 - December 2023, totaling 2249. The sampling technique used is purposive sampling using the Slovin formula, so the number of samples in this study were 96 respondents. Based on the results of this research, it shows that partially the influence of Digital Marketing (X1) has a positive and significant effect on Consumer Loyalty at Pulma House Medan. The influence of Customer Relationship Marketing (X2) has a positive and significant effect on Consumer Loyalty at Pulma House Medan. Based on the results of the F Test, it was found that Digital Marketing and Customer Relationship Marketing together (simultaneously) had an effect on Consumer Loyalty. In the coefficient of determination (R2), the Adjusted R Square value obtained is 0.829 (82.9%) and the remaining 17.1% will be influenced by other factors that cannot be explained in this research.